Institutions, policies and economic performance - Brunner, Karl; Meltzer, Allan H. (Amsterdam ; New York : North-Holland Pub. Co., 1976)
This volume contains papers presented at the 1974 and 75 Carnegie-Rochester Conferences. The papers discuss the policies recommended by the Joint Economic Committee (JEC) of the U.S. Congress and by the Organization fro Economic Co-operation and Development (OECD). The papers analyze the purposes served and the policies chosen by one of the principal agencies concerned with thrift institutions, the Federal Home Loan Bank Board (FHLBB). The papers further test some alternative theories of inflation and compare policies and the outcomes of policies in several countries.
Carnegie-Rochester conference series on public policy; Volume 4.
Includes bibliographical references..
ne 06/07/2018
Loans
Keywords: Inflation (Finance); United States